TRANSFORMATION OF THE SYSTEM OF PUBLIC FINANCIAL CONTROL IN THE CONDITIONS OF MARKET TRANSFORMATIONS - IVANCHENKOVA, Larysa; SKLIAR, Larysa; TKACHUK, Halyna; HNATIEVA, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The aim of the article is to analyze the development of the system of public financial control in Ukraine by studying the theoretical and methodological and organizational principles of its formation and operation. The state cannot function and develop effectively without a clearly organized system of control over the production, distribution and redistribution of social product and other spheres of public life. Therefore, the most important in this regard is the established system of public financial control, which should ensure balance and equilibrium in the functioning of society.The main task of the system of state control is to increase the effective activities of public authorities to protect the interests of the state and its citizens by strengthening the responsibility of these bodies and their officials for the performance of their duties. The processes taking place in the field of public financial control are different in nature and ambiguous, and sometimes contradictory, affect the formation of its system.It is established that an important tool of public administration, which allows to achieve these tasks and reduce the number of problematic issues related to the activities of government agencies, is public financial control, which should ensure proper (legal, economic, efficient, effective and transparent) management public finances, their harmonization. State financial control is provided by the state financial control body through public financial audit, inspection, procurement verification and procurement monitoring.It is noted that the effectiveness of public financial control largely depends on the welfare of the people, for which one of the most important functions of public administration should be aimed at identifying deviations from accepted standards of legality, feasibility and efficiency of financial resources and public property and the timely taking of appropriate adjustments and precautions. Systematic and comprehensive control helps to ensure the scientific validity of decisions, regulations and other regulatory documents, their timely implementation.
Keywords: state financial control; system of state financial control bodies; control; state financial audit; finance